Effect of technological innovation on firm’s performance: mediating effect of competitive advantage: a study on manufacturing firms operating in Ethiopian industrial parks - Kumera, Dula; Amentie, Chalchissa; Bali, Neeraj (Brazilian Journal of Operations & Production Management, 2024)
Goal: This study aims to examine the relationship between technological innovation and the performance of manufacturing firms operating in Ethiopian industrial parks through the mediating effect of competitive advantage. Design/Methodology/Approach: A mixed research-methods approach and an explanatory research design were applied to explore the relationship between the variables of the study. By using the non-probability sampling technique, the researchers collected data from 382 top and middle managers and purified it through Confirmatory Factor Analysis. To examine the effect of technological innovation and test the hypothesis, this study employed Structural Equation Modeling (SEM). Result: The findings supported that technological innovation positively and significantly influences firms’ performance (b = 0.483, p<0.001) and competitive advantage (b = 0.583, p<0.001). Moreover, it is exposed that competitive advantage influences firm performance (b = 0.379; p<0.001). Thus, the result demonstrated that the proposed partial mediation model was accepted because the relationship between the constructs was statistically significant. The result confirms that improving technological innovation enables increased product quality and process efficiency, which leads to minimizing operational costs and offering quality products that improve firms’ success. Limitations: The proposed model may not be generalized due to one-time data collection. Thus, it should be implemented in other business environments. The study is also limited to publicly owned industrial parks. Hence, future studies can incorporate privately owned industrial parks. Practical Implication: This study reveals that firm managers must give attention to technological innovation and develop differentiated competitive advantages to improve firm performance. Further, policymakers are suggested to establish systematic monitoring and evaluation for effective technology transfer and knowledge spillover between local employees and foreign employees. Originality/value: This study adds value to the current body of knowledge by addressing the mediating effect of competitive advantage in the relationship between technological innovation and firm performance.